To block or not to block? : a meta-analysis of effectiveness of block-based programming - Talan, Tarik; Dogan, Yunus; Kalinkara, Yusuf; Batdi, Veli (Routledge Journals, Taylor & Francis Ltd, 2025)
BackgroundBlock-based programming applications have gained increasing attention in education for their potential to enhance students' academic achievement, problem-solving abilities, and computational thinking skills. Despite their widespread use across grade levels and subject areas, there is limited meta-analytic evidence synthesizing their overall impact and identifying conditions under which they are most effective.MethodsThis meta-analysis examined studies published between 2001 and 2024 that investigated the effects of block-based programming applications on students' academic achievement. Effect sizes were calculated using Hedges' g, and moderator analyses were conducted to test differences based on educational level, subject area, sample size and intervention duration.ResultsThe overall findings indicate that block-based programming has a moderate positive effect on academic achievement (g = 0.53). Moderator analyses showed no statistically significant differences across educational levels, subject areas, or sample sizes. However, the strongest effects were observed among elementary students, suggesting that the visual and interactive nature of block-based tools particularly supports cognitive development at early ages. The interventions were most effective when implemented for 5-6 weeks, and Science-related applications yielded the greatest gains, helping students understand abstract concepts and improve problem-solving abilities. Medium-sized groups benefited the most, likely due to balanced interaction and engagement.ConclusionBlock-based programming applications positively influence students' academic achievement across diverse educational contexts. While the findings highlight their effectiveness especially in Science education, elementary settings, and mid-sized groups, further research is needed to examine their long-term impacts and their applicability across additional subject areas. Educators and policymakers are encouraged to integrate block-based programming into curricula to enhance learning outcomes.
Keywords: Block-based programming; text-based programming; programming instruction; meta-analysis; computational thinking